2012
DOI: 10.1088/0004-637x/747/1/81
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Far-Ir Line Deficit: Photoelectric Heating and Far-Ir Line Cooling in NGC 1097 and NGC 4559

Abstract: The physical state of interstellar gas and dust is dependent on the processes which heat and cool this medium. To probe heating and cooling of the interstellar medium over a large range of infrared surface brightness, on sub-kiloparsec scales, we employ line maps of [C ii] /PAH drops rapidly to 4%. We derived representative values of the local ultraviolet radiation density, G 0 , and the gas density, n H , by comparing our observations to models of photodissociation regions. The ratio G 0 /n H , derived from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
108
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 83 publications
18
108
1
Order By: Relevance
“…The , as well as a decrease with FIR color in star-forming galaxies (Malhotra et al 2001). Several hypotheses to explain the apparent line deficit in galaxies include (1) more dust screening at high ionization parameter (Luhman et al 2003;Abel et al 2009); (2) lower photoelectric efficiency due to charged small dust grains under intense radiation fields (Malhotra et al 2001;Croxall et al 2012); (3) lower photoelectric efficiency due to a decrease in the PAH abundance under hard radiation fields (Madden et al 2006;Rubin et al 2009); and (4) large dust optical depths leading to extinction of the emission lines (Papadopoulos et al 2010;Rangwala et al 2011). The dwarf galaxies extend the relative importance of the gas cooling to high values.…”
Section: Interpretation Of the [C Ii]/l Tir And [O I]/l Tir Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The , as well as a decrease with FIR color in star-forming galaxies (Malhotra et al 2001). Several hypotheses to explain the apparent line deficit in galaxies include (1) more dust screening at high ionization parameter (Luhman et al 2003;Abel et al 2009); (2) lower photoelectric efficiency due to charged small dust grains under intense radiation fields (Malhotra et al 2001;Croxall et al 2012); (3) lower photoelectric efficiency due to a decrease in the PAH abundance under hard radiation fields (Madden et al 2006;Rubin et al 2009); and (4) large dust optical depths leading to extinction of the emission lines (Papadopoulos et al 2010;Rangwala et al 2011). The dwarf galaxies extend the relative importance of the gas cooling to high values.…”
Section: Interpretation Of the [C Ii]/l Tir And [O I]/l Tir Trendsmentioning
confidence: 99%
“…From those studies (see Genzel & Cesarsky 2000, for a review), the [C ] line emerges as the brightest cooling line of the ISM in star-forming galaxies and as a good tracer of the star formation activity, accounting for ∼0.1-1% of the FIR luminosity (e.g., Stacey et al 2010;Pierini et al 2003;Boselli et al 2002;De Looze et al 2011, 2014aSargsyan et al 2014). A deficit in the FIR line intensities is, however, found in luminous IR galaxies (e.g., Luhman et al 2003;Graciá-Carpio et al 2011;Croxall et al 2012;Díaz-Santos et al 2013). The origin of the [C ] line has been debated in extragalactic studies as it can arise from molecular, neutral atomic, and ionized gas phases.…”
Section: Introductionmentioning
confidence: 99%
“…The model assumes a plane parallel slab geometry illuminated from one direction with a specified 1D UV field and calculates the thermal balance and abundances of the dominant atomic and molecular species as well as their line emission. These models have been used to interpret a variety of observations of molecular and atomic species in a wide range of physical conditions including OH + , H 2 O + , and H 3 O + in diffuse gas (Hollenbach et al 2012), H 2 O and HF in diffuse gas (Sonnentrucker et al 2015), [C i] and CO in low UV field molecular clouds (Burton et al 2014;Lee et al 2014), H 2 in dense PDRs (Sheffer et al 2011) (Kaufman et al 2006;Croxall et al 2012).…”
Section: Numerical Pdr Modelsmentioning
confidence: 99%
“…However, studies have shown important differences between SMGs and ULIRGs. For example, the spatial extent of the gas and star formation in SMGs appears to be much larger than that typically seen in local ULIRGs (∼few kpc in SMGs compared to just hundreds of pc in local ULIRGs, e.g., Chapman et al 2004;Sakamoto et al 2008;Kennicutt et al 2011;Croxall et al 2012;Ivison et al 2012;Ikarashi et al 2015;Simpson et al 2015a;Hodge et al 2016), and while the intense star formation seen in local ULIRGs appears to be triggered by major mergers (e.g., Clements & Baker 1996;Farrah et al 2001;Surace et al 2001;Veilleux 2002), theoretical predictions have suggested that SMGs at z∼1-5 comprise a heterogeneous mix of star formation occurring in extended disks, pre-coalescence mergers, and late-stage mergers (e.g., Hayward et al 2011;Cowley et al 2017), which may be consistent with Hubble Space Telescope (HST) imaging (Chen et al 2015).…”
Section: Introductionmentioning
confidence: 98%